Potential of Corn Stover And Coconut Shell as Environmentally Friendly Biomass Alternative Fuel - Budiyanto, Ratno; Setiawati, Titin; Rahem, Abd. (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Energy sources from non-renewable materials such as petroleum are limited and will continue to decrease. Meanwhile, efforts to find renewable energy sources as reserves require quite expensive costs with a relatively long duration. Therefore, it is necessary to research renewable energy sources, such as corn stovers and coconut shells. This study is generally carried out by making charcoal or carbonization, briquetting, and testing the quality of briquettes. The variables used in this study are the composition of corn cob charcoal and coconut shells. The composition of the mixture used consists of 5 comparative variables, namely sample A = 1: 1, sample B = 1: 2, sample C = 1: 3, sample D = 2: 1, and sample E = 3: 1 with a drying temperature of 100 oC. This study aims to produce biobriquettes from variations in the ratio of good and quality corn cob and coconut shell so that they can be used as environmentally friendly alternative fuels. This study concludes that the optimal mixture variation to produce good quality biobriquettes is found in sample C with a water content of 2.20%, ash content of 3.22%, sulfur content of 0.07%, and a calorific value of 7339 cal/gram because it has a lower optimization compared to other samples and meets the specified standards.